HUBUNGAN POLA MAKAN DENGAN KEJADIAN SINDROMA DISPEPSIA FUNGSIONAL PADA REMAJA DI MADRASAH ALIYAH NEGERI MODEL MANADO - Susilawati, .; Palar, Stella; Waleleng, Bradley J. (e-CliniC, 2013)
Abstract: The relation of eating patterns with Genesis Functional Dyspepsia Syndrome in Adolescents in MAN Model Manado. Thesis, Medical Faculty of the University of Sam Ratulangi Manado. Counselor  dr. B.J.Waleleng, SpPD-KGEH, Advisor  dr. Stella Palar, SpPD-KGH.Dyspepsia syndrome is collection of symptoms of pain or discomfort in the upper abdomen that episodic. It is very common among the public, especially in adolescents. Syndrome dyspepsia have dysfunctional and  organic.Dyspepsia syndrome is caused by various factors, one of which is irregular eating patterns. The aims of  this study is to determine the extent of the relationship between diet and incidence of dyspepsia syndrome in young students MAN Model Manado Research is descriptive study conducted analytic survey by using questionnaires. Study sample 50 adolescents aged 16-17 years who attend school in MAN Model Manado. Purposive sampling method. The results showed irregular eating frequency 48%, and spicy foods  much 70%. Incidence of dyspepsia syndrome  the overall sample 96%. And the analysis demonstrated an association with eating syndrome incidence of dyspepsia in MAN Model Manado.Adolescents are expected to pay attention to their eat patterns and be more disciplined in managing the daily feeding schedule  day. Keywords: diet, dyspepsia syndrome, adolescents   Abstrak: Hubungan Pola Makan dengan Kejadian Sindroma Dispepsia Fungsional pada Remaja di Madrasah Aliyah Negeri Model Manado. Skripsi, Fakultas kedokteran Universitas Sam Ratulangi Manado. Pembimbing dr. B.J.Waleleng, SpPD-KGEH, Pembimbing dr.Stella Palar, SpPD-KGH.Sindroma dispepsia adalah kumpulan gejala nyeri atau rasa tidak enak di abdomen atas yang episodik. Hal ini sangat umum di kalangan masyarakat khususnya pada remaja. Sindroma dispepsia mempunyai kelainanan fungsional dan organik.Sindroma dispepsia disebabkan oleh berbagai faktor, salah satunya adalah pola makan yang tidak teratur. Pada penelitian ini bertujuan untuk mengetahui sejauh mana hubungan antara pola makan dengan kejadian  sindroma dispepsia pada siswa remaja di MAN Model ManadoPenelitian deskriptifanalitik dengan survei menggunakan kuisioner.Sampelpenelitian 50 orang remaja yang berusia 16 – 17 tahun yang bersekolah di Madrasah Aliyahnegeri Model Manado. Sampel diambil dengan metode purposive sampling. Hasil penelitian menunjukkan frekuensi makan yang tidak teratur 48%, dan mengkonsums imakanan pedas sebanyak 70%. Angka kejadian sindroma dyspepsia dari keseluruhan sampel  96%. Hasil analisis menunjukkan terdapat hubungan pol amakan dengan kejadian sindroma dyspepsia pada remaja di MAN Model Manado. Diharapkan remaja dapat memperhatikan pola makannya dan lebih disiplin dalam mengatur jadwal makan sehari – hari. Kata kunci: pola makan, sindroma dispepsia, remaja